Prototype Sistem Deteksi Dini Kebakaran Hutan (Sd2kh) dengan Sensormatik - Agung Setiawan; Budi Yanto (Prosiding SISFOTEK, 2018)
The island of Sumatra, especially Riau province every year continues to be encroached forest land into plantation land. This land conversion is generally done by burning the land for plantations, resulting in a national disaster in the form of forest fires. The condition of the land in Riau province is largely peat land and resulted in the difficulty of being extinguished during a fire, especially if the fire condition is large and spread. With the condition of peat lands, forest fires have a wider impact with the smoke haze that is difficult to overcome, thus becoming a national disaster. Weather conditions that are increasingly extreme dry season due to global warming, resulting in forest fires become more severe and affect all aspects of community life and animals in the forest. To solve the above problem, we need a detection tool which in the research will be made sistem deteksi dini kebakaran hutan (SD2KH) connected with Internet of Things (IoT), and integrated with mobile phone number of related agencies through SMS gateway. With this tool, it is hoped that the handling of smoke will soon be handled by the relevant agencies, so that the impact of smoke will not become widespread and become a national disaster.